Method for modifying hexagonal boron nitride by ozone
Through the surface modification of hexagonal boron nitride after low temperature heat treatment and ozone oxidation treatment, the existing modification methods have been solved, and the ozone modification with environmental protection and good modification effect has been achieved. The production of hexagonal boron nitride improves the fluidity and bondability of the product.
Patent Information
- Application Number
- CN202411694532.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-18
AI Technical Summary
The existing hexagonal boron nitride modification methods have problems such as complex process, high cost, environmental pollution, poor modification effect and production stability.
The hexagonal boron nitride after low temperature heat treatment is mixed with water to make a slurry, ozone is passed for oxidation treatment, and then modified with a surf modifier to obtain modified hexagonal boron nitride.
It realizes ozone modified hexagonal boron nitride with simple operation, environmental protection, good modification effect and stable mass production, which improves the fluidity and bondability of the product and meets the requirements of practical application.
Smart Images

Figure CN119463532A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic filler modification methods and relates to a method for ozone modification of hexagonal boron nitride. Background Art
[0002] Since the surface of boron nitride lacks active groups, it is necessary to introduce functional groups on its surface through modification to facilitate its subsequent further application. The existing methods for modifying hexagonal boron nitride have the following problems: (1) The wet modification process is complex, costly, and the solvents used will pollute the environment; (2) Although the dry modification method is environmentally friendly and simple, it cannot achieve uniform mixing, resulting in poor modification effects and cannot meet the requirements for the fluidity and bonding of hexagonal boron nitride in practical applications; (3) The gas phase method, mechanical method, and radiation method all have production stability issues.
[0003] Chinese patent CN107324296B discloses a method for modifying hexagonal boron nitride, wherein the boron nitride pretreated with nitric acid is dispersed in a mixed aqueous solution of formic acid and sulfuric acid and irradiated with gamma rays to obtain hydroxyl-modified boron nitride. This method uses both a wet method and a radiation method, and the acidic solution involved is expensive and difficult to handle, and irradiation can cause product stability problems.
[0004] Chinese patent CN116082858A discloses a boron nitride modification method, product and application, wherein boron nitride powder and fumed silica powder are mixed and then heated and cured, so that silica coats the boron nitride, and then modified with a silane coupling agent. However, the introduction of silica affects the purity of the product, thereby affecting the product performance. Summary of the invention
[0005] The object of the present invention is to provide a method for ozone-modified hexagonal boron nitride which is simple to operate, environmentally friendly, has good modification effect and can be stably produced in large quantities.
[0006] The technical solution for achieving the purpose of the present invention is as follows:
[0007] A method for ozone-modified hexagonal boron nitride, wherein the hexagonal boron nitride is subjected to low-temperature heat treatment and then mixed with water to form a slurry, then ozone is introduced for oxidation treatment, and finally a surface modifier is used for modification to obtain modified hexagonal boron nitride, and the specific steps are as follows:
[0008] (1) Low temperature heat treatment: heat treating the hexagonal boron nitride powder at 400-800°C in an air atmosphere to obtain heat-treated hexagonal boron nitride;
[0009] (2) preparing a boron nitride slurry: stirring and mixing the heat-treated hexagonal boron nitride and pure water to prepare a boron nitride slurry having a solid content of 10 to 30%;
[0010] (3) Ozone pretreatment: Under stirring, ozone is introduced into the boron nitride slurry for oxidation treatment. After the treatment, solid-liquid separation is performed, and the solid is dried to obtain the ozone pretreated boron nitride powder;
[0011] (4) Modification: Under heating conditions of 50 to 120° C., a surface modifier is added to the ozone pretreated boron nitride powder while stirring for modification, and after modification, the modified hexagonal boron nitride is obtained by drying and aging.
[0012] Preferably, in step (1), the treatment time is 4 to 6 hours.
[0013] Preferably, in step (2) or (3), the stirring frequency is 60 to 120 rpm.
[0014] Preferably, in step (3), the ozone gas flow rate is 1 to 10 L / min, the concentration is 12 to 50 mg / L, and the oxidation treatment time is 24 to 48 h.
[0015] Preferably, in step (3), the drying temperature is 90 to 110° C. and the drying time is 2 to 8 hours.
[0016] Preferably, in step (4), the mass of the surface modifier accounts for 0.1% to 2% of the mass of the hexagonal boron nitride powder, and the modification time is 20 min to 60 min.
[0017] Preferably, in step (4), the surface modifier is selected from epoxy silane coupling agent, acyloxy silane coupling agent, silazane coupling agent, etc., such as KH-560 silane coupling agent, γ-methacryloxypropyltrimethoxysilane, hexamethyldisilazane, etc.
[0018] Preferably, in step (4), the drying and aging temperature is 80 to 110° C., and the drying and aging time is 2 to 8 hours.
[0019] After the hydrolyzable groups in the surface modifier combine with the hydroxyl groups on the surface of boron nitride, more carbon-containing long chains are combined on the surface of boron nitride, so the more modifiers are added, the higher the carbon content; the excess free modifiers can be removed by butanone, and the tested carbon content at this time is the content of the modifier grafted to the surface of boron nitride. The higher the carbon content, the more surface modifiers are successfully grafted. The carbon content is also related to the carbon content of the modifier.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] (1) The present invention first performs low-temperature heat treatment on hexagonal boron nitride, and the edges of the hexagonal boron nitride after heat treatment are slightly oxidized to provide more active sites for modification; then the hexagonal boron nitride is made into a slurry and then oxidized with ozone. Ozone can be fully dissolved in water and slowly decomposed into oxygen and hydroxyl radicals in water. The hydroxyl radicals react with the empty orbitals in the hexagonal boron nitride, and the BN bonds of the hexagonal boron nitride are destroyed to expose the B site, thereby promoting the generation of B-OH, thereby increasing the activity of the hexagonal boron nitride and uniformly oxidizing the boron nitride powder.
[0022] (2) The present invention adopts an ozone oxidation method to pretreat boron nitride, avoiding the use of a large amount of organic solvents and the decomposition of ozone into oxygen, thereby reducing environmental pollution and improving environmental protection.
[0023] (3) The modification method of the present invention is simple and convenient, and different modifiers can be selected according to actual needs, thereby achieving the diversity of modifiers, expanding the application range of hexagonal boron nitride, and reducing production costs and improving production efficiency.
[0024] (4) The method of the present invention improves the fluidity and bonding of modified hexagonal boron nitride in the corresponding system, meeting the requirements for the fluidity and bonding of hexagonal boron nitride in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the infrared spectrum of hexagonal boron nitride obtained in Example 8. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below with reference to specific embodiments.
[0027] In the following examples and comparative examples, infrared spectra and carbon content of modified samples were tested, and carbon content of powders after excess free modifiers were cleaned with butanone was tested; the modified samples were mixed with epoxy resin and the maximum filling amount and thermal conductivity at the maximum filling amount were tested.
[0028] Infrared testing method: Use Fourier infrared spectrometer for detection. All chemical bonds in molecules have specific vibration frequencies. These vibration frequencies can match the wavelength of infrared light. Therefore, molecules absorb specific frequencies of infrared light, thereby generating peaks for detection.
[0029] Carbon content: The carbon and sulfur analyzer from Germany, Inductar CS cube, is used to burn the carbon and sulfur in the sample through high-temperature induction to generate carbon dioxide and sulfur dioxide gases, and then an infrared detector is used to detect the concentration of these gases to calculate the carbon content in the sample.
[0030] Thermal conductivity: Use Hunan DRL-Ⅲ thermal conductivity meter to test. Under stable conditions, unidirectional heat flow passes vertically through the sample. The thermal conductivity of the sample is calculated based on the temperature of 6 points on the upper and lower thermal conductive rods, the effective heat transfer area and the thickness.
[0031] Example 1
[0032] The hexagonal boron nitride powder was heat treated at 600℃ in air atmosphere for 4h to obtain the heat-treated hexagonal boron nitride. The heat-treated hexagonal boron nitride and pure water were stirred and mixed evenly to prepare a boron nitride slurry with a solid content of 15%. Ozone with a gas flow rate of 5L / min and a concentration of 24mg / L was introduced into the boron nitride slurry with a stirring speed of 10Hz. After oxidation treatment for 36h, the solid-liquid separation was carried out and the ozone-pretreated boron nitride powder was obtained by drying at 100℃ in an oven for 8h. Under heating conditions of 60℃, 0.5% KH-560 silane coupling agent was added to the ozone-pretreated boron nitride powder, stirred for 20min, and dried and aged at 90℃ in an oven for 8h to obtain modified hexagonal boron nitride. The carbon content before and after modification and after cleaning with butanone was tested, and the maximum filling amount and thermal conductivity at the maximum filling amount were tested after the modified sample was mixed with epoxy resin. The test data show that the boron nitride product modified by the method has a high coupling agent grafting efficiency, thus having a higher maximum filling amount and thermal conductivity.
[0033] Example 2
[0034] The hexagonal boron nitride powder was heat treated at 400℃ in air atmosphere for 4h to obtain the heat-treated hexagonal boron nitride. The heat-treated hexagonal boron nitride and pure water were stirred and mixed evenly to prepare a boron nitride slurry with a solid content of 15%. Ozone with a gas flow rate of 5L / min and a concentration of 24mg / L was introduced into the boron nitride slurry with a stirring speed of 10Hz. After oxidation treatment for 36h, the solid-liquid separation was carried out and the ozone-pretreated boron nitride powder was obtained by drying at 100℃ in an oven for 8h. Under heating conditions of 60℃, 0.5% KH-560 silane coupling agent was added to the ozone-pretreated boron nitride powder, stirred for 20min, and dried and aged at 90℃ in an oven for 8h to obtain modified hexagonal boron nitride. The carbon content before and after modification and after cleaning with butanone was tested, and the maximum filling amount and thermal conductivity at the maximum filling amount were tested after the modified sample was mixed with epoxy resin. Compared with Example 1, after lowering the heat treatment temperature, the grafting amount of the coupling agent is slightly reduced, so that the maximum filling amount and the thermal conductivity are also reduced.
[0035] Example 3
[0036] The hexagonal boron nitride powder was heat treated at 800℃ in air atmosphere for 4h to obtain the heat-treated hexagonal boron nitride. The heat-treated hexagonal boron nitride and pure water were stirred and mixed evenly to prepare a boron nitride slurry with a solid content of 15%. Ozone with a gas flow rate of 5L / min and a concentration of 24mg / L was introduced into the boron nitride slurry with a stirring speed of 10Hz. After oxidation treatment for 36h, the solid-liquid separation was carried out and the ozone-pretreated boron nitride powder was obtained by drying at 100℃ in an oven for 8h. Under heating conditions of 60℃, 0.5% KH-560 silane coupling agent was added to the ozone-pretreated boron nitride powder, stirred for 20min, and dried and aged at 90℃ in an oven for 8h to obtain modified hexagonal boron nitride. The carbon content before and after modification and after cleaning with butanone was tested, and the maximum filling amount and thermal conductivity at the maximum filling amount were tested after the modified sample was mixed with epoxy resin. Increasing the heat treatment temperature will make the boron nitride surface more thermally activated, but the improvement effect is very small compared with Example 1, so its maximum filling amount is similar to that of Example 1.
[0037] Example 4
[0038] The hexagonal boron nitride powder was heat treated at 600℃ in air atmosphere for 4h to obtain the heat-treated hexagonal boron nitride. The heat-treated hexagonal boron nitride and pure water were stirred and mixed evenly to prepare a boron nitride slurry with a solid content of 15%. Ozone with a gas flow rate of 1L / min and a concentration of 12mg / L was introduced into the boron nitride slurry with a stirring speed of 10Hz. After 24h of oxidation treatment, the solid and liquid were separated and dried in an oven at 100℃ for 8h to obtain the ozone-pretreated boron nitride powder. Under heating conditions of 60℃, 0.5% KH-560 silane coupling agent was added to the ozone-pretreated boron nitride powder, stirred for 20min, and dried and aged in an oven at 90℃ for 8h to obtain modified hexagonal boron nitride. The carbon content before and after modification and after cleaning with butanone was tested, and the maximum filling amount and thermal conductivity at the maximum filling amount were tested after the modified sample was mixed with epoxy resin. After reducing the ozone gas flow rate and concentration, the coupling agent grafting amount decreased, resulting in a decrease in the maximum filling amount and thermal conductivity.
[0039] Example 5
[0040] The hexagonal boron nitride powder was heat treated at 600℃ in air atmosphere for 4h to obtain the heat-treated hexagonal boron nitride. The heat-treated hexagonal boron nitride and pure water were stirred and mixed evenly to prepare a boron nitride slurry with a solid content of 15%. Ozone with a gas flow rate of 10L / min and a concentration of 50mg / L was introduced into the boron nitride slurry with a stirring speed of 10Hz. After oxidation treatment for 48h, the solid-liquid separation was carried out and the ozone-pretreated boron nitride powder was obtained by drying at 100℃ in an oven for 8h. Under heating conditions of 60℃, 0.5% KH-560 silane coupling agent was added to the ozone-pretreated boron nitride powder, stirred for 20min, and dried and aged at 90℃ in an oven for 8h to obtain modified hexagonal boron nitride. The carbon content before and after modification and after cleaning with butanone was tested, and the maximum filling amount and thermal conductivity at the maximum filling amount were tested after the modified sample was mixed with epoxy resin. Increasing the ozone flow rate and concentration can make the oxidation of boron nitride more thorough, but the effect is similar to that of Example 1, and the coupling agent grafting limit has been reached.
[0041] Example 6
[0042] The hexagonal boron nitride powder was heat treated at 600℃ in air atmosphere for 4h to obtain the heat-treated hexagonal boron nitride. The heat-treated hexagonal boron nitride and pure water were stirred and mixed evenly to prepare a boron nitride slurry with a solid content of 10%. Ozone with a gas flow rate of 5L / min and a concentration of 24mg / L was introduced into the boron nitride slurry with a stirring speed of 10Hz. After oxidation treatment for 36h, the solid-liquid separation was carried out and the ozone-pretreated boron nitride powder was obtained by drying at 100℃ in an oven for 8h. Under heating conditions of 60℃, 2% KH-560 silane coupling agent was added to the ozone-pretreated boron nitride powder, stirred for 20min, and dried and aged at 90℃ in an oven for 8h to obtain modified hexagonal boron nitride. The carbon content before and after modification and after cleaning with butanone was tested, and the maximum filling amount and thermal conductivity at the maximum filling amount were tested after the modified sample was mixed with epoxy resin. The results show that the binding sites have been completely grafted after boron nitride pretreatment, and further increasing the coupling agent content cannot increase the carbon content of boron nitride after butanone cleaning.
[0043] Example 7
[0044] The hexagonal boron nitride powder was heat treated at 600℃ in air atmosphere for 4h to obtain the heat-treated hexagonal boron nitride. The heat-treated hexagonal boron nitride and pure water were stirred and mixed evenly to prepare a boron nitride slurry with a solid content of 30%. Ozone with a gas flow rate of 5L / min and a concentration of 24mg / L was introduced into the boron nitride slurry with a stirring speed of 10Hz. After oxidation treatment for 36h, the solid-liquid separation was carried out and the ozone-pretreated boron nitride powder was obtained by drying at 100℃ in an oven for 8h. Under heating conditions of 60℃, 0.5% γ-methacryloxypropyltrimethoxysilane was added to the ozone-pretreated boron nitride powder, stirred for 20min, and dried and aged at 90℃ in an oven for 8h to obtain modified hexagonal boron nitride. The carbon content before and after modification and after cleaning with butanone was tested, and the maximum filling amount and thermal conductivity at the maximum filling amount were tested after the modified sample was mixed with epoxy resin. From the results, this method can also achieve the same effect after replacing the silane coupling agent.
[0045] Example 8
[0046] The hexagonal boron nitride powder was heat treated at 600℃ in air atmosphere for 4h to obtain the heat-treated hexagonal boron nitride. The heat-treated hexagonal boron nitride and pure water were stirred and mixed evenly to prepare a boron nitride slurry with a solid content of 10%. Ozone with a gas flow rate of 5L / min and a concentration of 24mg / L was introduced into the boron nitride slurry with a stirring speed of 10Hz. After oxidation treatment for 36h, the solid-liquid separation was carried out and the ozone-pretreated boron nitride powder was obtained by drying at 100℃ in an oven for 8h. Under heating conditions of 60℃, 0.5% hexamethyldisilazane was added to the ozone-pretreated boron nitride powder, stirred for 20min, and dried and aged at 90℃ in an oven for 8h to obtain modified hexagonal boron nitride. The infrared spectrum of the powder before and after modification, the carbon content before and after modification and after cleaning with butanone were tested, and the maximum filling amount and the thermal conductivity at the maximum filling amount were tested after the modified sample was mixed with epoxy resin. Compared with the infrared spectrum of the original powder, it can be seen that at 2960cm -1 A new absorption peak appears, which is attributed to the CH vibration absorption peak of CH3. This phenomenon indicates that the coupling agent has been grafted successfully.
[0047] Comparative Example 1
[0048] Hexagonal boron nitride and pure water were stirred and mixed evenly to prepare a boron nitride slurry with a solid content of 15%. Under heating conditions at 60°C, 0.5% KH-560 silane coupling agent was added to the boron nitride slurry, stirred for 20 minutes, and then dried and aged in an oven at 90°C for 8 hours to obtain modified hexagonal boron nitride. The carbon content before and after modification and after cleaning with butanone was tested, and the modified sample was mixed with epoxy resin to test the maximum filling amount and thermal conductivity at the maximum filling amount. The coupling agent grafting amount of the product directly modified without pretreatment was significantly reduced, resulting in extremely low maximum filling amount and thermal conductivity.
[0049] Comparative Example 2
[0050] The hexagonal boron nitride powder was heat treated at 600°C in air atmosphere for 4 hours to obtain the heat-treated hexagonal boron nitride. Under heating conditions at 60°C, 0.5% KH-560 silane coupling agent was added to the pretreated boron nitride powder, stirred for 20 minutes, and dried and aged in an oven at 90°C for 8 hours to obtain modified hexagonal boron nitride. The carbon content before and after modification and after cleaning with butanone was tested, and the modified sample was mixed with epoxy resin and tested for the maximum filling amount and thermal conductivity at the maximum filling amount. Compared with Example 1, the maximum filling amount of the modified boron nitride that was not pretreated with ozone decreased by 12% and the thermal conductivity decreased by 37%.
[0051] Comparative Example 3
[0052] Hexagonal boron nitride powder and pure water were stirred and mixed evenly to prepare a boron nitride slurry with a solid content of 15%. Ozone with a gas flow rate of 10L / min and a concentration of 50mg / L was introduced into the boron nitride slurry with a stirring speed of 10Hz. After 48h of oxidation treatment, the solid and liquid were separated and dried in an oven at 100°C for 8h to obtain the boron nitride powder pretreated with ozone. Under heating conditions of 60°C, 0.5% KH-560 silane coupling agent was added to the boron nitride powder pretreated with ozone, stirred for 20min, and dried and aged in an oven at 90°C for 8h to obtain modified hexagonal boron nitride. The carbon content before and after modification and after cleaning with butanone was tested, and the maximum filling amount and thermal conductivity at the maximum filling amount were tested after the modified sample was mixed with epoxy resin. Compared with Example 1, the maximum filling amount of the modified boron nitride that was not heat treated decreased by 10% and the thermal conductivity decreased by 32%.
[0053] Comparative Examples 2 and 3 show that the best effect can be achieved by combining heat treatment with ozone pretreatment.
[0054] Comparative Example 4
[0055] The hexagonal boron nitride powder was heat treated at 300℃ in air atmosphere for 4h to obtain the heat-treated hexagonal boron nitride. The heat-treated hexagonal boron nitride and pure water were stirred and mixed evenly to prepare a boron nitride slurry with a solid content of 15%. Ozone with a gas flow rate of 10L / min and a concentration of 50mg / L was introduced into the boron nitride slurry with a stirring speed of 10Hz. After oxidation treatment for 48h, the solid-liquid separation was carried out and the ozone-pretreated boron nitride powder was obtained by drying at 100℃ in an oven for 8h. Under heating conditions of 60℃, 0.5% KH-560 silane coupling agent was added to the ozone-pretreated boron nitride powder, stirred for 20min, and dried and aged at 90℃ in an oven for 8h to obtain modified hexagonal boron nitride. The carbon content before and after modification and after cleaning with butanone was tested, and the maximum filling amount and thermal conductivity at the maximum filling amount were tested after the modified sample was mixed with epoxy resin. Heat treatment below 400° C. did not achieve the activation effect on boron nitride, similar to Comparative Example 3, so the coupling agent grafting success rate was low.
[0056] Comparative Example 5
[0057] The hexagonal boron nitride powder was heat treated at 900℃ in air atmosphere for 4h to obtain the heat-treated hexagonal boron nitride. The heat-treated hexagonal boron nitride and pure water were stirred and mixed evenly to prepare a boron nitride slurry with a solid content of 15%. Ozone with a gas flow rate of 10L / min and a concentration of 50mg / L was introduced into the boron nitride slurry with a stirring speed of 10Hz. After oxidation treatment for 48h, the solid-liquid separation was carried out and the ozone-pretreated boron nitride powder was obtained by drying at 100℃ in an oven for 8h. Under heating conditions of 60℃, 0.5% KH-560 silane coupling agent was added to the ozone-pretreated boron nitride powder, stirred for 20min, and dried and aged at 90℃ in an oven for 8h to obtain modified hexagonal boron nitride. The carbon content before and after modification and after cleaning with butanone was tested, and the maximum filling amount and thermal conductivity at the maximum filling amount were tested after the modified sample was mixed with epoxy resin. Heat treatment at over 800°C oxidizes the boron nitride, generates more boron oxide on the surface, and increases the number of coupling agent grafting sites. Therefore, the carbon content increases after cleaning with butanone, but the thermal conductivity of boron oxide is low.
[0058] The carbon content of the powder before and after modification, the carbon content after cleaning with butanone, the maximum filling amount mixed with epoxy resin and the thermal conductivity at the maximum filling amount in the embodiments and comparative examples are shown in Table 1.
[0059] Table 1
[0060]
Claims
1. A method for ozone-modified hexagonal boron nitride, characterized in that: The specific steps are as follows: (1) Low temperature heat treatment: heat-treating the hexagonal boron nitride powder at 400-800°C in an air atmosphere to obtain heat-treated hexagonal boron nitride; (2) Preparing boron nitride slurry: stirring and mixing the heat-treated hexagonal boron nitride and pure water to prepare a boron nitride slurry with a solid content of 10-30%; (3) Ozone pretreatment: Ozone is introduced into the boron nitride slurry under stirring for oxidation treatment. After the treatment, solid-liquid separation is performed and the solid is dried to obtain the ozone pretreated boron nitride powder; (4) Modification: Under heating conditions of 50-120°C, a surface modifier is added to the boron nitride powder after ozone pretreatment while stirring for modification. After modification, the powder is dried and aged to obtain modified hexagonal boron nitride.
2. The method according to claim 1, characterized in that In step (1), the processing time is 4 to 6 hours.
3. The method according to claim 1, characterized in that In step (2) or (3), the stirring speed is 60-120 rpm.
4. The method according to claim 1, characterized in that: In step (3), the ozone flow rate is 1-10 L / min, the concentration is 12-50 mg / L, and the oxidation treatment time is 24-48 h.
5. The method according to claim 1, characterized in that In step (3), the drying temperature is 90-110° C. and the drying time is 2-8 hours.
6. The method according to claim 1, characterized in that In step (4), the mass of the surface modifier accounts for 0.1% to 2% of the mass of the hexagonal boron nitride powder, and the modification time is 20 min to 60 min.
7. The method according to claim 1, characterized in that In step (4), the surface modifier is selected from epoxy silane coupling agent, acyloxy silane coupling agent or silazane coupling agent.
8. The method according to claim 1, characterized in that In step (4), the surface modifier is selected from KH-560 silane coupling agent, γ-methacryloxypropyltrimethoxysilane or hexamethyldisilazane.
9. The method according to claim 1, characterized in that: In step (4), the drying and aging temperature is 80-110° C., and the drying and aging time is 2-8 hours.
Citation Information
Patent Citations
Modification methods of hexagonal boron nitride and hydroxyl-modified boron nitride
CN107324296B
Boron nitride modification method, product and application
CN116082858A
Cited By
Preparation method of modified BN two-dimensional catalytic material and application of modified BN two-dimensional catalytic material in methane conversion
CN120325313A
Preparation method of modified BN two-dimensional catalytic material and its application in methane conversion
CN120325313B